Soft Selling Communications Strategies in Building Brand Awareness for “Sasa” on Raditya Dika’s YouTube Account Content - Ilham Baihaqi; Salsabila Cahyarani; Farida Nurfalah (CV. Media Digital Publikasi Indonesia, 2025)
Marketing in the modern era, namely soft selling, is characterized by the use of digital technology and a more personal approach. This research aims to find out the soft selling communication strategy applied by Sasa in building brand awareness, especially in the promotion of vetsin (MSG) through collaboration with Raditya Dika on YouTube in the content